2015
DOI: 10.1111/papr.12327
|View full text |Cite
|
Sign up to set email alerts
|

Problems in Functioning in Patients with Chronic Musculoskeletal Pain Admitted for Multidisciplinary Rehabilitation

Abstract: A 15-week multidisciplinary treatment program showed that most problems were seen within chapters Mobility and Community life of the ICF. The program led to significant improvements of patient reported problems, the magnitude of which was similar for all different problem areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The present study concerned the long‐term follow‐up of a prospective, observational study, from which the short‐term data had been published previously (Koele et al, ; Meesters et al, ). All data were gathered routinely and stored in electronic patient records in connection with a standardized multidisciplinary team care intervention for patients with CMP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study concerned the long‐term follow‐up of a prospective, observational study, from which the short‐term data had been published previously (Koele et al, ; Meesters et al, ). All data were gathered routinely and stored in electronic patient records in connection with a standardized multidisciplinary team care intervention for patients with CMP.…”
Section: Methodsmentioning
confidence: 99%
“…Given the scarcity of studies on the long‐term effects of multidisciplinary treatment for CMP in daily practice, the aim of the present study was to describe the outcomes comprehensively – that is, in terms of pain, physical function, work status and health care utilization in the long term (24 months). The presentanalysis was a follow‐up of two previous reports from our group describing the problems of patients with CMP admitted to a 15‐week rehabilitation programme and its effects on pain, activities and participation at discharge (Koele et al, ; Meesters et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The COPM is a reliable standardised assessment with strong test‐retest reliability (Carswell et al, 2004). A change score of two points on the COPM is considered as a clinically important change (Law et al, 2015; Meesters et al, 2016; Nieuwenhuizen, Groot, Janssen, Der, & Beckerman, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps this has contributed to the inattention to or unawareness of this issue. However, the phenomenon that clients identify issues on all levels, including tasks or actions, have previously been seen in stud-ies of the COPM [40][41][42][43]. In a study of Poulsen and Hansen, a vast number of the identified OPIs were classified in the lower levels of the TCOP [41].…”
Section: The Opis Of Danish Clientsmentioning
confidence: 99%